Drop size distribution in a complete 'warm' shower process (MAUSAM, 1960)
A theoretical discussion of (i) overall raindrop size distribution and (ii) rate of decrease of maximum drop size towards end stages of a 'warm' shower process, based on collision-cum-coalescence theory of rain drop growth is represented. A comparison is made of the theoretical deductions with some of the observational findings.